Comparative study on the effectiveness of rwh system in different types of building - Nur Aimi Fakhira, Mat Zain (2014)
RWH system is a norm practice in village and rural areas. It is done by collecting rainwater from rooftop and stored for domestic usage, such as washing and bathing. Since Malaysia received a stable rainfall throughout the year, the government realized that the RWH system can be used to resolve water shortage issue. Hence, the government provides a suitable guideline toward this issue. This paper will cover the effectiveness of the RWH system in different types of building such as office building, houses, HT Presswork Factory, commercial building, SJK Chung Hua 2 and Bukit Indah Mosque. There are few factors that influenced the effectiveness of the kWH system such as roof area, building function and location of buildings. Another factor that affects effectiveness is the number of, user or employee, size and capacity of the tank and lastly cost of the system. From the study, the most effective RWH system is on office building because the number of employee and demand are small. The capital cost is also considerably low due to the location factor where the office building is located in a rural area but still have a higher percentage of water saving with low capital cost. Contrarily, this system is not economically for the HT Presswork Factory buildings as its installation cost is higher compared to the percentage of water savings.